THE ROLE OF ISCHEMIC MYOCARDIAL WALL DAMAGE ON THE CLINICAL COURSE OF UNSTABLE ANGINA PECTORIS IN MEN OF WORKING AGE (World Bulletin of Public Health, 2024)
In this work, the clinical features of the course of unstable angina pectoris were studied depending on ischemic myocardial damage in patients at a young age. 150 patients with unstable angina pectoris were examined on the basis of the Samarkand regional branch of the Republican Scientific and Practical Specialized Medical Center of Cardiology. All patients, depending on their age, were divided into 2 groups: the first main group consisted of 76 young patients. The second comparative group consisted of 74 elderly patients. The most common occurrence of angina attacks from 6 to 8 times during the day was observed in 55 (67.5%) patients of group 1, in 52 (78.8%) patients in group 2, which indicated the severity of the disease. According to ECG data, ischemic lesion of more than two walls was most often observed in young people, and scarring was most often observed in older men, this was due to a previous history of AMI
Keywords: unstable angina pectoris; young age; old age; ischemia